IMPROVING STUDENTS NARRATIVE READING COMPREHENSION THROUGH GUIDED READING FOR JUNIOR HIGH SCHOOL - Rahadian Suryanta; Fitrawati Fitrawati (Universitas Negeri Padang, 2016)
This paper explains about the implementation of “Guided Reading” startegy in teaching reading especially in teaching narrative text. In this stategy, the teacher chooses the text which is appropriate with the students’ ability and the teacher uses a picture to develop their background knowledge. Guided Reading strategy is begun by dividing the students into some groups that consist of 3-4 members. After that, the teacher distributes the text to each member of the group and prepares students to read the text by developing their background knowledge, knowing the vocabulary from the text, and knowing the purpose of reading the text. After knowing the purpose of reading the text, students read the text silently in order to increase the students’ concentration. After reading the text, the teacher provides worksheets that contain assignments to connect the story (narrative text) with the students’ experience and discuss it in group. Then, the student asks to rewrite the story which is helped by answering some questions that have been provided by the teacher. The last, the teacher gives tests to the students to find out their understanding and comprehending about the text. By using this strategy, the students are hoped having better English reading skill especially in reading narrative text.